2011
DOI: 10.1103/physrevlett.106.210801
|View full text |Cite
|
Sign up to set email alerts
|

Lattice-Induced Frequency Shifts in Sr Optical Lattice Clocks at the1017Level

Abstract: We present a comprehensive study of the frequency shifts associated with the lattice potential in a Sr lattice clock by comparing two such clocks with a frequency stability reaching 5×10(-17) after a 1 h integration time. We put the first experimental upper bound on the multipolar M1 and E2 interactions, significantly smaller than the recently predicted theoretical upper limit, and give a 30-fold improved upper limit on the effect of hyperpolarizability. Finally, we report on the first observation of the vecto… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
152
0
6

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 139 publications
(163 citation statements)
references
References 20 publications
5
152
0
6
Order By: Relevance
“…This strong confinement regime (Lamb-Dicke regime) dramatically reduces the motional effects. The lattice induces a light shift of several 10 5 Hz on the energy levels, but, as anticipated in the initial proposal 9 , we can control the differential shift at the mHz level 22 when the lattice is operated at the magic wavelength. Together with the J ¼ 0 nature of the clock states, this leads to a spectroscopy almost immune to fluctuations in trapping power or polarization.…”
Section: Olc Architecturementioning
confidence: 99%
See 3 more Smart Citations
“…This strong confinement regime (Lamb-Dicke regime) dramatically reduces the motional effects. The lattice induces a light shift of several 10 5 Hz on the energy levels, but, as anticipated in the initial proposal 9 , we can control the differential shift at the mHz level 22 when the lattice is operated at the magic wavelength. Together with the J ¼ 0 nature of the clock states, this leads to a spectroscopy almost immune to fluctuations in trapping power or polarization.…”
Section: Olc Architecturementioning
confidence: 99%
“…With a waist of 56 mm and an intracavity power of 14 W, the second clock features potentials as deep as 5000 E r . The magic frequency, f magic ¼ 368,554,725 (5) MHz, ensures only the cancellation of the scalar part of the differential polarizability; a tensor correction 22 depending on the angle a between the lattice polarization and the quantization axis defined along the magnetic field can shift noticeably the effective magic point (from f magic À 268 MHz to f magic þ 134 MHz). This angle also defines the sensitivity of the clocks to residual lattice polarization fluctuations.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…It enabled us to explore systematic effects induced by the trapping laser light. These effects are specific to OLCs, and we have demonstrated that they can be controlled to better than 10 −17 , even with a significant trapping depth [27,28], thus validating the concept of OLCs. In particular, we have determined the precise value for the "magic wavelength" for which the impact of the trapping light is canceled to first order, and resolved or upperbounded a number of higher order effects.…”
Section: Optical Lattice Clocksmentioning
confidence: 83%